2019
DOI: 10.1016/j.jclepro.2019.04.128
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of nanoparticles for the remediation of contaminated waters and soils: Constituents, synthesizing methods, and influencing factors

Abstract: Green synthesis of nanoparticles for the remediation of contaminated waters and soils: constituents, synthesizing methods, and influencing factors, (2019),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(40 citation statements)
references
References 108 publications
0
37
0
3
Order By: Relevance
“…Green and sustainable remediation (GSR) is a new movement in the land and groundwater remediation field that has drawn much attention globally in recent years, and it requires consideration of the environmental, economic, and social dimensions of sustainability. GSR technologies for contaminated groundwater, including biochar materials, green synthesis of engineered nanoparticles [52], sustainable PRB [53] and sustainably released long-term green remediation materials, have made rapid progress. However, case studies indicate that public participation must be improved to promote social sustainability, and region-specific factors should be considered when implementing GSR.…”
Section: Discussionmentioning
confidence: 99%
“…Green and sustainable remediation (GSR) is a new movement in the land and groundwater remediation field that has drawn much attention globally in recent years, and it requires consideration of the environmental, economic, and social dimensions of sustainability. GSR technologies for contaminated groundwater, including biochar materials, green synthesis of engineered nanoparticles [52], sustainable PRB [53] and sustainably released long-term green remediation materials, have made rapid progress. However, case studies indicate that public participation must be improved to promote social sustainability, and region-specific factors should be considered when implementing GSR.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the initial pH value has a significant impact on the removal rate of Cr(VI) in soil, no matter what kind of nZVI is wrapped by modified materials [74]. More specifically, the pH value and the Cr(VI) removal rate show a negative correlation [75], that is, with the rising pH value, the Cr(VI) removal rate declines [76].…”
Section: Effect Of the Initial Ph Valuementioning
confidence: 98%
“…[Gallocatechin-(4alpha->8)]2-catechin and Cinnamtannin A3) also have antibacterial properties [78][79][80], indicating a stressor on the growth of certain bacteria in the permafrost. We highlight the fact that certain metabolites are naturally produced by microbial fermentation of plant residues (see epicatechin production by the fermentation of green tea in Jiang et al [81] which explains the presence of plant producing metabolites in our samples.…”
Section: Plos Onementioning
confidence: 99%